Effects of bending strain and crack direction on crack-based strain sensors. (22nd September 2020) - Kwon, Yongmin; Park, Chan; Kim, Jungmin; Kim, Hyonguk; Park, Cheoljeong; Lee, Byeongjun; Jeong, Yeondo; Cho, Seong J
Abstract: Inspired by the sensory organs of spiders, crack-based strain sensors are flexible sensors fabricated by depositing a thin layer of metal onto a stretchable polymer. However, to date, most studies on crack-based sensors have considered only linear strain, even when bending is considered, which do not analyze how sensor resistance depends on complex strains (linear, convex, and concave). For each given type of strain, this study examined how the distance between cracks depends on the crack direction. This study also analyzed how the crack-generation mechanism depends on the relation between film-bending axis and crack direction. Thus, a device was proposed herein to test the crack-based sensors and demonstrate how this device can be used to measure the bending direction.